The metabolic phenotype of SCD1-deficient mice is independent of melanin-concentrating hormone - Glier, Melissa B. (2009)
We propose that deletion of pro-melanin-concentrating hormone (pMCH) would increase energy expenditure and further improve glucose tolerance in mice lacking stearoyl-coA desaturase-1 (SCD1). To test our hypothesis, we bred and metabolically challenged Pmch−/−; Scd1−/− double-knockout mice, with comparison to Pmch−/− mice; Scd1−/− mice and C57Bl/6J controls. Deletion of both Pmch and Scd1 increased both food intake and energy expenditure relative to control mice. Pmch−/−; Scd1−/− double-knockout mice had improved glucose tolerance relative to control mice. The majority of the metabolic effects were contributed by inactivation of the Scd1 gene. Weconclude that the increased food intake and increased energy expenditure of Scd1−/− mice are independent of the neuropeptide melanin-concentrating hormone.